Perspectives of Cancer Survivors with Low Income: A Content Analysis Exploring Concerns, Positive Experiences, and Suggestions for Improvement in Survivorship Care - Irene Nicoll; Gina Lockwood; Margaret I. Fitch (Current Oncology, 2023)
The number of cancer survivors in Canada has reached 1.5 million and is expected to grow. It is important to understand cancer survivors’ perspectives about the challenges they face after treatment is completed. Many factors create barriers to accessing assistance, and limited income may be a significant one. This study is a secondary analysis of data from a publicly available databank (Cancer Survivor Transitions Study) regarding the experiences of Canadian cancer survivors. The goal was to explore major challenges, positive experiences, and suggestions for improvement in survivorship care for low-income Canadian cancer survivors one to three years following treatment. A total of 1708 survey respondents indicated a low annual household income (<$25,000 CD). A content analysis was performed utilizing written comments to open-ended questions. The major challenges respondents described focused on physical capacity limits and treatment side effects; positive experiences emphasized support and attentive care; and suggestions for improvements highlighted the need for better support, information about self-care and side effect management, and timely follow-up care. The relationships between household income and the management of survivors’ physical, emotional, and practical concerns require consideration. The design of follow-up care plans, programs, services, and financial assessments of patients may prepare survivors for predictable issues and costs in their transition to survivorship.